Vinegar elaboration from cherry fruit discard (Prunus cerasus L.) - Loyola, Nelson; Lagos, Sergio; Acuña, Carlos; Arriola, Mariela (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The production of vinegar from the fermentation of cherry (Prunus cerasus) discard was experimentally evaluated. Four treatments were used: filtered vinegar, unfiltered vinegar, pasteurized vinegar and vinegar with metabisulfite. The physicochemical and organoleptic characteristics and their acceptability were determined through a completely randomized experimental design with three (3) repetitions per treatment. The data were analyzed according to an analysis of variance, with a 95% confidence level to determine possible significant differences between the treatments. The parameters were measured; soluble solids, density, pH, sodium chloride and acidity. Also, a sensory analysis of the attributes was carried out; color, aroma, texture and flavor, with 33 trained panelists, in order to evaluate the organoleptic characteristics and acceptance of each of the samples. The cherry vinegar prepared and evaluated after 5, 20 and 35 days did not show significant differences in its physicochemical characteristics. The panelists perceived more differences in sensory attributes when the vinegar was pasteurized according to the treatment (T2). The panelists did not vary their perception of the acceptability of vinegar, regardless of the treatment applied.